Perampasan Tanah dan Perlawanan Petani: Dampak Perkebunan Sawit terhadap Kehidupan Masyarakat di Pasaman Barat Tahun 1980-2022 - Radiatul Adawiyah; Zaiyardam Zubir; Hary Efendi (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
This research examines "Land Grabbing and Farmer Resistance: The Impact of Oil Palm Plantations on People’s Life in West Pasaman during 1980-2022". Forests belonging to indigenous peoples encountered land grabbing and conversion into oil palm plantations. Land grabbing is a common phenomenon in West Pasaman.  The purpose of this research are  to find out the pattern of land ownership in West Pasaman from 1980-2022, strategy of land grabbing, the resistance of oil palm farmers, Fourthly, and the impact of the widespread land grabbing activities on oil palm plantations in West Pasaman. This research used a multidimensional approach. For this reason, social science theories such as economics, anthropology and sociology were used to explain the subject matter. This method strategy is important to be able to analyze the research topic more comprehensively. The method used was historical method including heuristics, criticism, interpretation, and historiography.  The result of research shows that the expansion of oil palm plantations is putatively more than 70% of land in West Pasaman controlled by large companies, while the rest of 30% is for the people in West Pasaman. Large plantations did land acquisition successfully in various ways such as buying land, cooperation with traditional leaders, and land grabbing. The land grabbing results in various effects: people losing their land, displaced communities, poverty, no place to stand and farmer resistance. In conclusion, the expansion of oil palm plantations has generated various conflicts within community. The main sources of conflict are land grabbing and socio-economic inequality in the community. This then led to the farmer’s resistance against the rulers and entrepreneurs of oil palm plantations.